2022
DOI: 10.3390/ma15155314
|View full text |Cite
|
Sign up to set email alerts
|

Blown Composite Films of Low-Density/Linear-Low-Density Polyethylene and Silica Aerogel for Transparent Heat Retention Films and Influence of Silica Aerogel on Biaxial Properties

Abstract: Blown films based on low-density polyethylene (LDPE)/linear low-density polyethylene (LLDPE) and silica aerogel (SA; 0, 0.5, 1, and 1.5 wt.%) were obtained at the pilot scale. Good particle dispersion and distribution were achieved without thermo oxidative degradation. The effects of different SA contents (0.5–1.5 wt.%) were studied to prepare transparent-heat-retention LDPE/LLDPE films with improved material properties, while maintaining the optical performance. The optical characteristics of the composite fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Figure 8 b shows that, similar to the MD sample ( Figure 8 a), the stress-at-break value of the Al (2–8 wt.%)/LLDPE/CaCO 3 composite films slightly increases and the Al (8 wt.%)/LLDPE/CaCO 3 composite film exhibits the highest stress-at-break (2.67 MPa). In this case, the improvement in the tensile properties can be explained by considering the probable influence of Al on the molecular orientation during the film extrusion, along with the good matrix–particle adhesion [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 8 b shows that, similar to the MD sample ( Figure 8 a), the stress-at-break value of the Al (2–8 wt.%)/LLDPE/CaCO 3 composite films slightly increases and the Al (8 wt.%)/LLDPE/CaCO 3 composite film exhibits the highest stress-at-break (2.67 MPa). In this case, the improvement in the tensile properties can be explained by considering the probable influence of Al on the molecular orientation during the film extrusion, along with the good matrix–particle adhesion [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Figure 8a, the stress-at-break value of the LLDPE/CaCO3 composite film increases after incorporating Al (2-8 wt.%), and the composite with 8 wt.% of Al loading shows the highest stress-at-break (10.41 MPa). In this instance, the improvement in the tensile properties can be explained by considering the potential impact of Al on the molecular orientation during the extrusion along the MD, as well as the strong matrix-particle adhesion [32], therefore promoting the increase in the tensile strength of the composite film with the incorporation of the Al particles (2-8 wt.%). On the other hand, the stress-strain curves demonstrated that the strain-at-break value of the LLDPE/CaCO3 film increases from 76.15% to 138.03% with the incorporation of Al (2-8 wt.%).…”
Section: Sample Type T Onset (mentioning
confidence: 99%